Inflation Targeting Lite' in Small Open Economies : The Case of Mauritius. (IMF Working Papers; Working Paper ;, 2005)
This paper develops a new macrofinance model for small open economies, allowing the investigation of Mauritius's experience with 'inflation targeting lite' as described in Stone (2003). It finds that this monetary policy regime has been associated with a general reduction in inflation, principally through a reduction in inflation expectations. The credibility the Bank of Mauritius has established with its 'inflation targeting lite' regime has allowed it to shift from an emphasis on exchange rate targeting towards inflation targeting. By estimating a model in which the yield curve is modeled explicitly we are able to obtain estimates of inflation expectations.